Integrative Pedagogy and Didactic Models in Teaching History Through Islamic Education: Insights from Uzbekistan - Saodat Toshtemirova; Nilufar Koshanova; Zilola Khaydarova; Feruza Ilmurodova; Mahfuza Sadullaeva; Dilshoda Nurmukhammadova (Jurnal Pendidikan Islam, 2025)
This study investigates the implementation of integrative Islamic educational models in History teaching at an Islamic university in Uzbekistan, specifically focusing on the cluster system approach. It aligns with Uzbekistan’s educational reforms, examining how History education can be harmonized with national values and global standards through competency-based learning and the cluster system. The research utilized a qualitative approach with experimental trials involving 501 participants across various educational levels. Data were collected through surveys, classroom observations, and document analysis. The study explored innovative methods such as the “Sensor Station” (preschool), “Historical Event Simulation” (general education), “Mission” (academic lyceums), and the “SIIM method” (vocational education), integrating religious and historical content for student-centered learning. These methods promoted critical thinking, creativity, and independent inquiry through role-playing, group work, and interactive tasks. Results indicated that students in the experimental group, exposed to the cluster-integrative approach, showed significant improvement in historical understanding, academic performance, and spiritual growth compared to the control group using traditional methods. The study concludes that a cluster-integrative model rooted in Islamic educational principles is effective in fostering historical thinking, moral reasoning, and higher-order competencies, offering valuable insights for enhancing History education from preschool to higher education in both formal and non-formal contexts.